The “transitional moment” of Chilean education: The Comisión Nacional para la Modernización de la Educación (1994-1995) - Neut Aguayo, Sebastián (Education Policy Analysis Archives, 2021)
This text studies the most important institutional process for the generation of educational policies in the transition to democracy in Chile at the end of the 20th century: the Comisión Nacional para la Modernización de la Educación. The objective of this government initiative was to generate a political and ideological platform shared by the “national community” that would pave the way for educational reform. The Commission was hegemonized by the government and the right-wing opposition, in a context in which they had high control over a weakened civil society, and there were thin boundaries between the political and expert fields. Ideologically, the ideas of human capital and Catholic conservatism predominated. The recommended policies were aimed at strengthening the educational market, with a promoting and evaluating State. The text conceives education as a field of political and ideological dispute. The modes of political and ideological articulation are analyzed from the extensive review of written primary sources, especially the press, the reports of the instance and government decrees.